Guideline on Implementing Nutrition-sensitive Actions in the Agri-food Systems - Rasheed, Sabrina; Mahmood, Shehrin; Mizan, Arefin; Ahmed, Mohammad Wahid; Hasan, A M Rumayan; Islam Tisha, Khadija; Rahman Sakin, Zillur; Roy, Prantik; Nasrin, Towhida (WorldFish, 2024)
This guideline emphasizes integrating nutrition-sensitive actions across agri-food systems to combat malnutrition and improve livelihoods. It emphasizes fostering sustainability through community empowerment, capacity building, and integrated approaches linking agriculture, livelihoods, and market access. Early stakeholder engagement aligns goals and empowers vulnerable populations, while robust monitoring and reporting assess impact. Embedding nutritional goals throughout intervention design ensures sustainable, impactful outcomes through collaborative efforts with governments, NGOs, and private sectors.